2017
DOI: 10.1002/bjs.10408
|View full text |Cite
|
Sign up to set email alerts
|

Network meta-analysis of the effect of preoperative carbohydrate loading on recovery after elective surgery

Abstract: Carbohydrate loading before elective surgery conferred a small reduction in length of postoperative hospital stay compared with fasting, and no benefit in comparison with water or placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 71 publications
6
96
0
6
Order By: Relevance
“…In a recent meta‐analysis, a pooled analysis of patients that underwent various elective surgical procedures demonstrated a significant reduction in length of hospital stay for both high dose and low dose carbohydrate loading when compared to patients that were fasting (−1.7 and −1.4 days, respectively). However, in a subgroup analysis of patients that underwent major abdominal surgery, a significantly shorter length of hospital stay was only found for high dose carbohydrate loading when compared to both fasting (−1.7 days) and placebo or water (−1.4 days) . Only a pooled analysis was performed for insulin resistance, which demonstrated a significantly decreased insulin resistance in patients that received a high dose carbohydrate load when compared to both fasting and placebo or water .…”
Section: Perioperative Periodmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent meta‐analysis, a pooled analysis of patients that underwent various elective surgical procedures demonstrated a significant reduction in length of hospital stay for both high dose and low dose carbohydrate loading when compared to patients that were fasting (−1.7 and −1.4 days, respectively). However, in a subgroup analysis of patients that underwent major abdominal surgery, a significantly shorter length of hospital stay was only found for high dose carbohydrate loading when compared to both fasting (−1.7 days) and placebo or water (−1.4 days) . Only a pooled analysis was performed for insulin resistance, which demonstrated a significantly decreased insulin resistance in patients that received a high dose carbohydrate load when compared to both fasting and placebo or water .…”
Section: Perioperative Periodmentioning
confidence: 99%
“…The proposed mechanism is that carbohydrate loading causes an initial increase in insulin sensitivity when compared to a fasting state, which is believed to dampen surgery‐induced insulin resistance . However, randomized controlled trials and meta‐analysis that investigated the effects of carbohydrate loading came to inconsistent conclusions . In a recent meta‐analysis, a pooled analysis of patients that underwent various elective surgical procedures demonstrated a significant reduction in length of hospital stay for both high dose and low dose carbohydrate loading when compared to patients that were fasting (−1.7 and −1.4 days, respectively).…”
Section: Perioperative Periodmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, ingestion of an oral carbohydrate solution a few hours before esophagectomy is advised, as it is believed to cause an initial increase in baseline insulin sensitivity and in that way dampens surgery‐induced insulin resistance . Although randomized controlled trials were inconsistent, a recent meta‐analysis of studies including a variety of surgical procedures indicated that carbohydrate loading may be associated with a reduced length of hospital stay compared with placebo or fasting . While the reported carbohydrate doses are varying, an amount of 400 mL of 12.5% carbohydrate solution may be advised .…”
Section: Enhanced Recovery After Esophagectomy In the Preoperative Sementioning
confidence: 99%